Increasing risks of apple tree frost damage under climate change - Peter Pfleiderer; Inga Menke; Carl-Friedrich Schleussner (Climatic Change, 2019)
Anthropogenic climate change is affecting agriculture and crop production. The responses of horticultural and agricultural systems to changing climatic conditions can be non-linear and at times counter-intuitive. Depending on the characteristics of the system, the actual impact can arise as a result of a combination of climate hazards or compound events. Here, we show that compound events can lead to increased risk of frost damage for apple fruit trees in Germany in a 2 °C warmer world of up to 10% relative to present day. Although the absolute number of frost days is declining, warmer winters also lead to earlier blossom of fruit trees, which in turn can lead to regionally dependent increased risks of the occurrence of frost days after apple blossom. In southern Germany, warmer winters may also lead to an increase in years in which apple yield is negatively affected by a lack of sufficient amount of cold days to trigger the seasonal response of the trees. Our results show how cropping system responses to seasonal climate can lead to unexpected effects of increased risk of frost damage as a result of warmer winters. An improved understanding of ecosystem responses to changes in climate signals is important to fully assess the impacts of climate change.

Quantification of temperature persistence over the Northern Hemisphere land-area - Peter Pfleiderer; Dim Coumou (Climate Dynamics, 2018)